Salmonella enterica serovar typhimurium exploits inflammation to compete with the intestinal microbiota. - Bärbel Stecher; Riccardo Robbiani; Alan W Walker; Astrid M Westendorf; Manja Barthel; Marcus Kremer; Samuel Chaffron; Andrew J Macpherson; Jan Buer; Julian Parkhill; Gordon Dougan; Christian von Mering; et al. (PLoS Biology, 2007)
Most mucosal surfaces of the mammalian body are colonized by microbial communities ("microbiota"). A high density of commensal microbiota inhabits the intestine and shields from infection ("colonization resistance"). The virulence strategies allowing enteropathogenic bacteria to successfully compete with the microbiota and overcome colonization resistance are poorly understood. Here, we investigated manipulation of the intestinal microbiota by the enteropathogenic bacterium Salmonella enterica subspecies 1 serovar Typhimurium (S. Tm) in a mouse colitis model: we found that inflammatory host responses induced by S. Tm changed microbiota composition and suppressed its growth. In contrast to wild-type S. Tm, an avirulent invGsseD mutant failing to trigger colitis was outcompeted by the microbiota. This competitive defect was reverted if inflammation was provided concomitantly by mixed infection with wild-type S. Tm or in mice (IL10(-/-), VILLIN-HA(CL4-CD8)) with inflammatory bowel disease. Thus, inflammation is necessary and sufficient for overcoming colonization resistance. This reveals a new concept in infectious disease: in contrast to current thinking, inflammation is not always detrimental for the pathogen. Triggering the host's immune defence can shift the balance between the protective microbiota and the pathogen in favour of the pathogen.